Aus der Welt der Sanskrit-Inschriften. Anlässlich des Buches von Th. Damsteegt - Mayrhofer, M.
Epigraphical Hybrid Sanskrit, London 1978; 3. on Iranian names; 4. Ab-ba-te-ma etc. in Persepolis Treasury Tablets.